Lanthanide-doped zinc gallium oxide (ZnGa2O4) nanocrystals and their engineered photoluminescence - Kim, Kihyo; Kim, Kicheol; Kwon, Hyo-Geun; Kim, Sunghoon; Kim, Sang-Wook (Macromolecular research, 2025)
Zinc gallate (ZnGa 2 O 4 ) has been introduced in various studies as a good host phosphorescent material, and the change of its optical properties by ion doping has received much attention. However, ZnGa 2 O 4 is mostly synthesized through solid-state reactions, the reaction conditions of high temperature and pressure were required, and its low dispersibility often limited its applications. In this study, we synthesized normal spinel structured ZnGa 2 O 4 nanocrystals through a colloidal method. Lanthanide doping specifically with europium and terbium resulted in red (614 nm, photoluminescence quantum yield (PLQY): 2.2%) and green (545 nm, PLQY: 13.6%) emissions under 254 nm UV excitation. By applying the novel co-doping system of europium and terbium to the synthesis of colloidal ZnGa 2 O 4 for the first time, we were able to achieve various color conversions including green, red, and white by adjusting amount and ratio of lanthanide ions. Graphic Abstract PL emission spectra by adjusting the ratios of Eu 3+ and Tb 3+ doping and the CIE 1931 chromatography diagram of Eu 3+ and Tb 3+ co-doping system of ZnGa 2 O 4 nanocrystals